Epstein-Barr virus enters B cells and epithelial cells by different routes. - Miller, N (1992)
Epstein-Barr virus (EBV) infects two cell types, B lymphocytes and epithelial cells. Electron microscopic studies have shown that the virus fuses with the lymphoblastoid cell line Raji but is endocytosed into thin-walled non-clathrin-coated vesicles in normal B cells before fusion takes place. To compare early interactions of EBV with epithelial cells and B cells, a fluorescence dequenching assay of fusion was employed, using virus labeled either with the pH-insensitive probe octadecyl rhodamine B chloride (R18) or with 5(N-octadecanoyl) aminofluorescein (AF), which loses emission intensity at a pH below 7.4. Fusion of virus labeled with R18 could be monitored with B cells, Raji cells, and epithelial cells. Lowering the extracellular pH or pretreatment of cells with ammonium chloride or methylamine had no effect on these measurements. In contrast, fusion of virus labeled with AF could be measured with Raji cells and epithelial cells, but not with normal B cells unless cells were previously treated with ammonium chloride. Fusion of virus with normal B cells was inhibited with chlorpromazine, chloroquine, and sodium azide, but none of these reagents had any effect on fusion with Raji or epithelial cells. These results suggest that entry of EBV into nonpolarized suspensions of epithelial cells occurs by fusion at the cell surface, that EBV may be incapable of fusing with normal B cells unless it has first been endocytosed, and that pH appears to be irrelevant to either event. A combination of the two probes, R18 and AF, may have general use for determining the sites of entry of enveloped viruses that fuse in a pH-independent manner.